Arbuscular Mycorrhizal Fungi in Agriculture - New Insights 2023
DOI: 10.5772/intechopen.108537
|View full text |Cite
|
Sign up to set email alerts
|

AM Fungi as a Potential Biofertilizer for Abiotic Stress Management

Abstract: Climate change and agricultural practices like unrestricted utilization of insecticides especially fertilizer and pesticides have amplified the effects of inanimate stress on the productivity of crops and degraded the environment. The need of the hour is to adopt eco-friendly crop management techniques, including the usage of arbuscular mycorrhizal fungi (AMF). AMFs are frequently referred to as bio-fertilizers. Mycorrhiza improves the movement and absorption of nutrients from soils, thereby limiting the deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Most recent studies noted that AM-colonized plants are more vigorous than noncolonized plants underneath salinity (Al-Karaki 2000). Previous research on the efficacy of AM during salinity stress showed that symbiosis of AM fungi positively affected nutrients uptake and signifies that the effect of salinity stress is controlled by AM fungi (Dastogeer et al 2020;Liu et al 2023;Aziz et al 2023). AM fungi effectively boost the availability of different macro and micronutrients, which improves photosynthetic efficiency and plant biomass (Chen et al 2017;Mitra et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies noted that AM-colonized plants are more vigorous than noncolonized plants underneath salinity (Al-Karaki 2000). Previous research on the efficacy of AM during salinity stress showed that symbiosis of AM fungi positively affected nutrients uptake and signifies that the effect of salinity stress is controlled by AM fungi (Dastogeer et al 2020;Liu et al 2023;Aziz et al 2023). AM fungi effectively boost the availability of different macro and micronutrients, which improves photosynthetic efficiency and plant biomass (Chen et al 2017;Mitra et al 2020).…”
Section: Introductionmentioning
confidence: 99%